1974
DOI: 10.1073/pnas.71.11.4541
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Molecular Weight of the 60-70S RNA and the 30-40S RNA of the Rous Sarcoma Virus

Abstract: The structure and molecular weight of the 60-70S RNA complex and the 30-40S RNA species of Rous sarcoma virus were analyzed in an electron microscope after treatment of the RNAs with the bacteriophage T4 gene-32 protein to stretch out the RNA strands. Although all RNA preparations treated with gene-32 protein showed considerable heterogeneity in length, a significant fraction of the RNA retained its original sedimentation coefficient after treatment to allow the following conclusions to be made: The 30-40S RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
42
0

Year Published

1980
1980
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 19 publications
(22 reference statements)
8
42
0
Order By: Relevance
“…Since the earliest investigations of retroviral RNAs (15), it has frequently been observed that dimeric RNAs appear intact even when they are composed of stochastically fragmented monomers (18). This observation shows that viral RNAs contain linkages other than the primary or most stable dimeric linkage but does not allow one to draw any inferences concerning the locations of these secondary linkages.…”
Section: Discussionmentioning
confidence: 99%
“…Since the earliest investigations of retroviral RNAs (15), it has frequently been observed that dimeric RNAs appear intact even when they are composed of stochastically fragmented monomers (18). This observation shows that viral RNAs contain linkages other than the primary or most stable dimeric linkage but does not allow one to draw any inferences concerning the locations of these secondary linkages.…”
Section: Discussionmentioning
confidence: 99%
“…Under less stringent conditions (Mangel et al, 1974) multiple points of contact have been noted, suggesting that the single linkage observed under more restrictive conditions might be a primary association or dimerization initiation site (DIS). Recent work from Ho$ glund et al (1997), looking at the dimer linkage of HIV-1 showed, interestingly, that there did not appear to be any free 5h ends, indicating that the two RNAs were interacting in addition at site(s) upstream of the recognized DLS.…”
Section: Rna Dimers and Dimer Linkage -The Evidencementioning
confidence: 99%
“…The structure of the mRNA for the putative precursor to the reverse transcriptase Prl80gag -p°~ has not yet been established, but information derived from the 0022-1317/83/0000-5704 $02.00 © 1983 SGM sequence of the Prague C strain genome RNA suggests the possibility that it is coded for by an approximately 9.3 kb RNA in which the termination codon for Pr76 ga0 is removed by splicing (D. Schwartz, personal communication). Besides these RNA species, additional 9.3 kb RNA molecules are packaged into virions as a dimeric 70S complex (Mangel et al, 1974). It is not yet clear whether the 9.3 kb RNA that is packaged is identical to the 9-3 kb mRNA.…”
Section: Introductionmentioning
confidence: 99%